Parametric Analysis on Heat Removal Factor for a Flat Plate Solar Collector of Serpentine Tube - Mohd Rosli, Mohd Afzanizam; Misha, Suhaimi; Sopian, Kamaruzzaman; Mat, Sohif; Sulaiman, M. Yusof; Salleh, Elias @ Ilias (IDOSI Publications, 2014)
The photovoltaic thermal (PVT) is a device that can produce electric and thermal energies simultaneously. The main components of PVT consist of the photovoltaic module, absorber collector, insulator, and mounting frame. The design of the absorber collector is crucial in the good performance of thermal energy. The heat removal factor FR, which is the ratio of the actual energy gain to the useful energy gain of a collecter when the entire collector surfaces are at the fluid inlet temperature, is one of the key parameters in determining the thermal efficiency of PVTs. A high FR means large thermal efficiency and losses and vice versa. In this study, the heat removal factor of four serpentine tubes with varying dimensions and profiles is analyzed. The rectangle tube shows the highest FR (0.93). This high FR value could be caused by the small diameter of the rectangle tube. In addition, a high number of tubes enhance the heat transfer between photovoltaic and serpentine collector absorber.